Cu and Si co-doping on TiO2 nanosheets to modulate reactive oxygen species for efficient photocatalytic methane conversion. Issue 1 (16th November 2022) - Ma, Jun; Low, Jingxiang; Wu, Di; Gong, Wanbing; Liu, Hengjie; Liu, Dong; Long, Ran; Xiong, Yujie
Abstract : The Cu and Si co-doping could rationally regulate the electronic structure of TiO2 nanosheets and maneuver the reactive oxygen species for methane activation, which achieves significant photocatalytic methane conversion into ethane. Abstract : In this study, we successfully construct Cu and Si co-doped ultrathin TiO2 nanosheets. As confirmed by comprehensive characterizations, Cu and Si co-doping can rationally tailor the electronic structure of TiO2 to maneuver reactive oxygen species for effective photocatalytic methane conversion. In addition, this co-doping greatly enhances the utilization efficiency of photogenerated charges. Furthermore, it is revealed that Cu and Si co-doping can significantly boost the adsorption and activation of methane on TiO2 nanosheets. As a result, the optimized catalyst achieves a C2 H6 production rate of 33.8 μmol g −1 h −1 with a selectivity of 88.4%. This work provides insights into nanocatalyst design toward efficient photocatalytic methane conversion into value-added compounds.